Decannulation in Acquired Brain Injury patients: the clinical impact of the process standardization. (30th September 2020) - d'Angelo, M; Michelutti, A; Biasutti, E; Quattrin, R
Abstract: Background: Decannulation is one of the first rehabilitation goals for Acquired Brain Injury (ABI) patients: from July 2017 the ABI unit of the Institute of Physical and Rehabilitation Medicine 'Gervasutta" adopted a decannulation protocol developed by the Italian Society of Physical Medicine and Rehabilitation (SIMFER). The current study aims to evaluate the impact of the process standardization on ABI patients. Methods: A retrospective case-control study was conducted: clinical outcome and hospitalization indicators in ABI patients with tracheal cannula were measured in reference to the decannulation procedure applied. Data were collected from patients' records from 2014 to 2017. SISA software was used for the statistical analysis. Results: A sample of 141 ABI patients was collected: among these 57 (40.4%) were treated with the new procedure. No statistically significant differences between control and case group were reported in terms of age, gender, aetiology of brain damage, cognitive and functional impairment as well as in terms of average days from admission to decannulation [39 (27); 35 (30)] and percentages of respiratory complications [20% vs 29.8%]. Decannulation rate was significantly higher in the case group (OR = 1.8; 95% CI = 1.2- 9.8; p < 0.01). Considering the case group, the simple linear regression analysis highlights a positive significant correlation between the length of hospitalization and days from decannulation to discharge (r = 0.3; p = 0.01) as well as from the date of oral feeding resumption and discharge (r = 0.4; p < 0.01). Conclusions: Higher decannulation rate with no increase in respiratory complications was registered with the introduction of the new protocol. The shortening of average days from patients' admission to decannulation, even if not statistically significant, as well as the results from the simple linear regression analysis probably highlights further advantages due to a major safety related to the presence of a decision algorithm. Key messages: The standardization of the decannulation process allowed the achievement of one of the first goals for the rehabilitation of Acquired Brain Injury (ABI) patients. The process standardization allowed a reduction of average days from patients' admission to decannulation, probably due to a major safety related to the presence of a decision algoritm.